2022
DOI: 10.1155/2022/5824429
|View full text |Cite
|
Sign up to set email alerts
|

Estimating the Need for Sedation in Patients with Dental Anxiety and Medical Complexities Reporting to Tertiary Care Dental Hospital Using the IOSN Tool

Abstract: Objectives. To provide consistent method for assessment of sedation need among patients undergoing dental treatment based on specific risk factors that is dental anxiety, medical status, and treatment complexity of needed dental treatment using IOSN (indication of sedation need) tool for assisting the clinician in decision making process. Methods. A total of 237 patients aged ≥12, ASA I and II were enrolled in the study. A structured questionnaire comprising of three sections was distributed among the particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…While it has been suggested that clinical guidelines often oversimplify treatment decision-making regarding implants, numerous studies highlighted the importance of considering multiple factors before selecting, preparing, or saving implants, particularly the patient’s medical history, bone quality, and implant location [ 30 , 75 , 76 , 77 ]. This was echoed by studies investigating surgical, extractive, and sedative decision making, which suggest consideration of patient factors such as medical history, including oncological prognosis and the level of dental anxiety [ 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While it has been suggested that clinical guidelines often oversimplify treatment decision-making regarding implants, numerous studies highlighted the importance of considering multiple factors before selecting, preparing, or saving implants, particularly the patient’s medical history, bone quality, and implant location [ 30 , 75 , 76 , 77 ]. This was echoed by studies investigating surgical, extractive, and sedative decision making, which suggest consideration of patient factors such as medical history, including oncological prognosis and the level of dental anxiety [ 78 , 79 , 80 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Dentists should consider the specifics of the individual patient, and assess the applicability of existing guidelines. The guidelines suggested by numerous studies emphasised patient-centred care and the importance of considering patient factors during treatment [ 75 , 76 , 78 , 81 ]. For example, a history of endocarditis and bisphosphonates may lead to a general refusal of implants [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that almost 20% of study participants were highly anxious due to undergoing dental procedures, and more than 30% of them had high sedation needs, which was significantly associated with the female sex, higher education status, and a history of previous traumatic dental experience. 30 Madouh and Tahmassebi conducted a similar study in the pediatric population. The study included 40 pediatric patients evaluated using the IOSN tool; out of them, 20 scored more than six and were subjected to more advanced methods of DS.…”
Section: Management Of Dental Fear and Anxietymentioning
confidence: 99%
“…For other patients who are cooperative but unable to maintain an open mouth for long periods, dental sedation may be used for procedures such as root canal therapy, surgical extractions, full mouth rehabilitation or extensive restorative work. 7 Additionally, depending on the patient and treatment needs, several routes of administration for dental sedation may be used: inhalation, intravenous, oral, intranasal and intramuscular. 8 A survey of dentists in the United States and Canada has revealed that 75.7% regularly use conscious sedation in practice; half reported using sedation as many as six times per month, and the other half reported using sedation more than six times per month.…”
Section: Introductionmentioning
confidence: 99%